Auxetic properties of some intermetallic compounds - Raransky, M.; Oliinych-Lysiuk, A.; Tashchuk, R.; Tashchuk, A.; Struk, A.; Unguryan, M. (Physics and Chemistry of Solid State, 2022)
With the application of a linear theory of elasticity of anisotropic crystals and the use of experimental values of elastic moduli Сij and compliances Sij given in the Landolt-Börstein tables, characteristic surfaces of Young's moduli, angular distributions of Poisson's ratios μ(φ, Θ, ψ) and indicating auxeticity surfaces of single crystals of intermetallic compounds Ag-Au, Cu-Ni, Cu-Au, and Cu-Zn were for the first time constructed. The extremely high sensitivity of the component of the extreme values of Young's moduli E<110> to anomalous deformations during phase transformations of the order-disorder type was established. Anomalies of the concentration dependences of the auxetic parameters μmin(X), μmax(X) and the auxeticity degree Sa(X) near the points of phase transformation of the second order type were revealed.